Untreated small posterior fragment of ankle fracture with early removal of syndesmotic screw is associated with recurrent syndesmotic instability. Issue 3 (March 2021) - Yang, Tzu-Cheng; Tzeng, Yun-Hsuan; Wang, Chien-Shun; Lin, Chun-Cheng; Chang, Ming-Chau; Chiang, Chao-Ching
Highlight: In cases of tri-malleolar fracture without PMF fixation, the syndesmotic screw should be removed at 3 months later. Syndesmotic instability should be kept in mind and intraoperative image examination must be performed for all cases with posterior malleolar fracture. Untreated posterior fragment of ankle fracture is regarded as a risk factor for recurrent syndesmotic diastasis Abstract: Introduction: This retrospective study aimed to report outcomes of fixation of bi-malleolar or tri-malleolar fractures combined with syndesmotic injury with or without posterior malleolar fracture (PMF), and to ascertain whether syndesmotic screw removal at 6 to 8 weeks or 3 months postoperatively is more beneficial. Methods: We retrospectively reviewed patients who received open reduction and internal fixation for bi-malleolar (without PMF) or tri-malleolar ankle fracture (with PMF) with syndesmotic injury between January 2013 and December 2017 with at least 24 months of postoperative follow-up. All patients suffered syndesmotic instabilities and were treated using a syndesmotic screw without PMF fixation. Patients with bi-malleolar fracture with syndesmotic screw removal at 6 to 8 weeks postoperatively were included in Group I, tri-malleolar fracture with syndesmotic screw removal at 6 to 8 weeks in Group II, and tri-malleolar fracture with syndesmotic screw removal at 3 months in Group III. Demographic data, clinical and radiographic outcomes were analyzed. Results: A total of 113 patients were included (Group I, n=47; Group II, n=43; Group III, n=23). Average size of PMF was 14% in patients with tri-malleolar fractures (Groups II and III). No significant difference in ankle functional outcome among groups was observed. The recurrence rate of syndesmotic instability was 10.6% in Group I, 20.9% in Group II, and 8.7% in Group III. Although the difference in recurrence rates of syndesmotic instability among three groups was not statistically significant ( P =0.264), Group II showed more interval change in tibiofibular clear space between initial postoperative radiographs and last follow-up radiographs ( P =0.028) compared to the other two groups. Fracture union was achieved in all patients without screw breakage. Conclusion: We suggest that the better timing for syndesmotic screw removal is 3 months, instead of 6 to 8 weeks postoperatively, to reduce the risk of recurrence of syndesmotic instability for tri-malleolar fracture without posterior fragment fixation. Level of Evidence: Level III- Case-control study.